3D printing in medicine - Kalaskar, Deepak M. (Woodhead Publishing, 2023)
3D Printing in Medicine, Second Edition examines the rapidly growing market of 3D-printed biomaterials and their clinical applications. With a particular focus on both commercial and premarket tools, the book looks at their applications within medicine and the future outlook for the field. The chapters are written by field experts actively engaged in educational and research activities at the top universities in the world. The earlier chapters cover the fundamentals of 3D printing, including topics such as materials and hardware. The later chapters go on to cover innovative applications within medicine such as computational analysis of 3D printed constructs, personalized 3D printing - including 3D cell and organ printing and the role of AI - with a subsequent look at the applications of high-resolution printing, 3D printing in diagnostics, drug development, 4D printing, and much more. This updated new edition features completely revised content, with additional new chapters covering organs-on-chips, bioprinting regulations and standards, intellectual properties, and socio-ethical implications of organs-on-demand.
Keywords: Biomedical materials -- Design.; Biomedical materials -- Technological innovations.; Three-dimensional printing.; elektronické knihy; electronic books